2019
DOI: 10.21037/tcr.2019.10.48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of icotinib on advanced lung adenocarcinoma patients with sensitive EGFR mutation detected in ctDNA by ddPCR

Abstract: Background: Whether or not EGFR mutation status detected by ddPCR in plasma predicts the effect of icotinib on patients with advanced lung adenocarcinoma was determined.Methods: Plasma and matched tissue specimens from patients with advanced lung adenocarcinoma were collected prior to icotinib treatment. The ARMS method was used to detect EGFR mutation status in DNA extracted from tissue specimens, while the EGFR mutation status in ctDNA extracted from plasma specimens was determined by ddPCR. The therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Accurate molecular typing is the basis of this precise treatment; however, qualified tumor tissue specimens cannot be obtained from every patient, so liquid biopsy was developed. Many studies have prospectively verified the high specificity (92–100%) and positive predictive value (94.0–98.6%) of ctDNA-based EGFR mutation detection using tissues as a reference [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and these two metrics have also been consistent in guiding the targeted therapy of NSCLC [ 30 , 31 , 34 , 35 ]. Recently, research on ctDNA-based next-generation sequencing (NGS) has demonstrated potential clinical utility [ 36 , 37 , 38 , 39 ].…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 98%
See 1 more Smart Citation
“…Accurate molecular typing is the basis of this precise treatment; however, qualified tumor tissue specimens cannot be obtained from every patient, so liquid biopsy was developed. Many studies have prospectively verified the high specificity (92–100%) and positive predictive value (94.0–98.6%) of ctDNA-based EGFR mutation detection using tissues as a reference [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and these two metrics have also been consistent in guiding the targeted therapy of NSCLC [ 30 , 31 , 34 , 35 ]. Recently, research on ctDNA-based next-generation sequencing (NGS) has demonstrated potential clinical utility [ 36 , 37 , 38 , 39 ].…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 98%
“…Table 1 presents data on the association between plasma ctDNA/cfDNA EGFR mutations and the efficacy and prognosis of targeted therapy in NSCLC patients [ 28 , 30 , 31 , 32 , 33 , 34 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The BENEFIT trial prospectively demonstrated the feasibility of using liquid biopsy to guide the efficacy of first-line EGFR-TKI therapy for the first time.…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 99%
“…However, tumor tissues for molecular profiling are not always available from advanced patients. Therefore, the use of tumor-derived cell-free DNA (cfDNA) isolated from body fluids, including plasma, pleural effusion (PE), cerebrospinal fluids, saliva, and urine, for cancer genomic profiling is being investigated (3)(4)(5)(6). Plasma derived cfDNA was widely accepted as a noninvasive option for tumor genomic profiling in patients with advanced stage malignancies, and also gained popularity for detecting tumor evolution and monitoring minimal residual disease in the era of precision medicine.…”
Section: Introductionmentioning
confidence: 99%